Solvent- and base-free synthesis of wax esters from fatty acid methyl esters by consecutive one-pot, two-step catalysis. Issue 23 (9th November 2017) - Nguyen, D. H.; Raffa, G.; Morin, Y.; Desset, S.; Capet, F.; Nardello-Rataj, V.; Dumeignil, F.; Gauvin, R. M.
Abstract : Wax esters were produced from fatty acid methyl esters using a catalytic one-pot, two-step sequence under solvent- and base-free conditions. Abstract : The one-pot, two-step synthesis of wax esters was successfully conducted by consecutive homogeneous ruthenium-catalysed hydrogenation–dehydrogenation reactions of fatty acid methyl esters, in the absence of solvent and of base additive. Under optimized conditions, excellent conversion and selectivity were reached. Furthermore, physicochemical investigations revealed that the resulting compounds display properties similar to benchmark commercial products extracted from natural sources of lesser availability compared to the herein considered bioresources, making this chemical route very promising regarding further potential industrial implementation.